Influence of the exchange and correlation functional on the structure of amorphous InSb and In3SbTe2 compounds - Gabardi, Silvia; Caravati, Sebastiano; Los, Jan H.; Kühne, Thomas D.; Bernasconi, Marco (Journal of Chemical Physics, 2016)
We have investigated the structural, vibrational, and electronic properties of the amorphous phase of InSb and In3SbTe2 compounds of interest for applications in phase change non-volatile memories. Models of the amorphous phase have been generated by quenching from the melt by molecular dynamics simulations based on density functional theory. In particular, we have studied the dependence of the structural properties on the choice of the exchange-correlation functional. It turns out that the use of the Becke-Lee-Yang-Parr functional provides models with a much larger fraction of In atoms in a tetrahedral bonding geometry with respect to previous results obtained with the most commonly used Perdew-Becke-Ernzerhof functional. This outcome is at odd with the properties of Ge2Sb2Te5 phase change compound for which the two exchange-correlation functionals yield very similar results on the structure of the amorphous phase.
CRIS-Team Scopus Importer:2023-03-20